Digital literacy research in scopus: A bibliometric analysis between 1997 and 2021 - Md Hafizi Ahsan; Saidatul Akmar Ismail; Masitah Ahmad; Sri Nurhayati (Researchgate, 2022)
Digital literacy has received much attention due to the proliferation of the use of technology in education and in workplace. People of all walks of life prefer to use electronic equipment to manage their daily routines and even social relationship. Thus, this paper attempts to put forth the key aspects of digital literacy within the research literature published between 1997 to 2021. This study pursued to (a) examine how digital literacy research has progressed, (b) determine what key areas are discussed in digital literacy, and (c) identify the major players in digital literacy research and their collaborations. Specifically, we analysed the progress of digital literacy research by examining (a) published studies, (b) source titles, (c) types of sources and documents, and (d) the languages in which the documents were written in, known as a bibliometric study. We also analysed the key areas of digital literacy research by looking into common subject areas, keywords used most often, and title analysis. Finally, we sought to increase our understanding of the major players in digital literacy research and their collaborations by examining (a) which countries contributed most to digital literacy research, (b), the main institutions involved, and (c) authorship and citation analysis.